Lung ultrasound for the diagnosis and monitoring of community-acquired pneumonia in children: a prospective observational study - Francavilla, M.; Scarlato, L.; Camporesi, A.; Orlandi, A.; Cafagno, C.; Raguseo, C. L.; Santoiemma, V.; Russo, R.; Sacco, A.; Musolino, A. M.; Supino, M. C.; Clemente, A.; et al. (Frontiers in Pediatrics, 2025)
IntroductionCommunity-acquired pneumonia remains a noteworthy concern in pediatrics due to the difficulty in identifying the underlying etiology and the risk of complications associated with high morbidity and mortality.MethodsThis is a multicenter, prospective study that enrolled 315 children admitted to three different hospitals in Italy between March 2023 and June 2024. The ultrasound scans were performed according to the approach proposed by Soldati et al. in 2020 at admission (T0) and during hospitalization (T1).ResultsLung ultrasound proved to be a valuable tool for differentiating etiologies, with significantly higher scores observed in bacterial and viral pneumonias compared to atypical cases (respectively p < 0.001 and p = 0.018). Furthermore, elevated ultrasound scores were predictive of adverse outcomes, such as the need for respiratory support or admission to the intensive care unit (p < 0.05). Finally, our findings highlight the importance of timing in follow-up assessments: a 72-hour interval was sufficient to detect improvements in lung ultrasound findings in severe cases (p < 0.01), while it appeared unnecessary in mild ones (p = 0.139).DiscussionThis study confirms the usefulness of lung ultrasound in monitoring children with community-acquired pneumonia and in the early identification of those at risk of clinical deterioration. Moreover, our findings offer useful guidance for optimizing follow-up timing, supporting personalized ultrasound approaches tailored to disease severity while reducing unnecessary examinations.